Performance Evaluation of Three Phase Spray Direct Contact Heat Exchanger - A. Jassim, Najim; A. Abdulkhaleq, Fatimah (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The present investigation deals with experimental study of three-phase direct-contact heat exchanger, for water-Freon R11 system, where water is the continuous phase (liquid) and Freon R11 (liquid-gas) is the dispersed phase. The test section consisted of a cylindrical Perspex column with inner diameter 8cm and 1.2m long, in which, water was to be confined. Liquid Freon R11 drops were injected into the hot water filled column, through a special design of distributors at the bottom of the column. The liquid Freon R11 drops rose on their way up and evaporated into two-phase bubbles at atmospheric pressure. The study was devoted to express the effect of process variables such as column height, Freon R11 mass flow rate and initial temperature of water on the average percentage holdup, heat transfer rate, volumetric heat transfer coefficient and effectiveness. The obtained experimental results showed that the average percentage holdup increased with increasing in the process variables. The heat transfer rate increased clearly with increasing in mass flow rate of Freon R11 while it increased very little when column height and initial temperature of water increased, it increased two times when increase the mass flow rate from 1.8 to 5.4 kg/hr. The volumetric heat transfer coefficient was found to decrease with increasing in column height and initial temperature of water, while it was increased with increasing in mass flow rate of Freon R11. The effectiveness was found to increase (maximum 90%) with increasing in column height and decreasing in the mass flow rate of Freon R11 and initial temperature of water. A statistical analysis was performed to get general correlations for the average percentage holdup, heat transfer rate, volumetric heat transfer coefficient and effectiveness as a function of the studied parameters.